\(S=1+2+2^2+...+2^9\)
\(\Rightarrow2S=2+2^2+2^3+...+2^{10}\)
\(\Rightarrow S=2^{10}-1\)
Lại có \(5.2^8=\left(2^2+1\right).2^8=2^{10}+2^8\)
Vậy \(S< 5.2^8\)
S=1+2+2^2+2^3+...+2^9
2S=2+2^2+2^3+...+2^9+2^10
2S-S=(2+2^2+2^3+...+2^9+2^10)-(1+2+2^2+2^3+...+2^9)
S=2^10-1
5.2^8=(2^2+1).2^8=(2^2.2^8)+(1.2^8)=2^10+2^8
Vì 2^10-1<2^10+2^8=> S<5.2^8
Vậy S < 5. 2^8
Ta có: \(S=1+2+2^2+2^3+...+2^9\)
\(\Rightarrow2S=2+2^2+2^3+...+2^{10}\)
\(\Rightarrow2S-S=\left(2+2^2+2^3+...+2^{10}\right)-\left(1+2+2^2+...+2^9\right)\)
\(\Rightarrow S=2^{10}-1\)
Mặt khác: \(5.2^8=\left(1+2^2\right).2^8=2^8+2^2.2^8=2^8+2^{10}\)
Vì \(2^{10}-1< 2^8+2^{10}\Rightarrow S< 5.2^8\)